Experimental setup of pipe whip impact - Shah, Qasim Hussain; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
Pipe whip is a safety related issue for nuclear power and chemical plants, where pipes are often used to transport fluids at high pressure and high temperature. Experiment works for empty pipe and liquid filled pipe are needed in this study. The model was made of simple pipe whip system which enables the missile pipe to hit the target pipe at an angle of 90° and also 55° oblique impact. The possible damages occur on the target pipe when the missile pipe hit it at certain velocity depend on the different mass of dropper and different diameter ofthe target pipe. Copper pipe is used as the target pipe and steel as the missile pipe